Preparation method of semiconductor ionic gel microspheres
By preparing semiconductor ion gel microspheres, the problems of low catalytic efficiency and susceptibility to photocorrosion of semiconductor quantum dots are solved, and the effect of improving catalytic capacity and delaying photocorrosion is achieved.
Patent Information
- Application Number
- CN202411818038.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The catalytic efficiency of semiconductor quantum dots is low and is susceptible to photocorrosion, which affects the reuse rate of materials.
A method of preparing semiconductor ionic gel microspheres is adopted to generate CdS semiconductor quantum dots by reaction of CdCl2·2.5H2O and 3-mercaptopropionic acid, and the ionic liquid is bound to the pores of mesoporous titanium dioxide. Microsphere-shaped semiconductor ionic gel composite materials are prepared by reverse phase emulsion polymerization technology.
The catalytic capacity of semiconductor quantum dots is improved, effectively prevents the loss of ionic liquid, delays the photocorrosion of semiconductor materials, and improves the reuse rate of materials.
Smart Images

Figure CN119633906A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion gel composite material preparation, and particularly relates to a method for preparing semiconductor ion gel microspheres. Background Art
[0002] Ion gels are composed of ionic liquids and supporting networks, and exhibit a variety of excellent properties, such as high mechanical strength, excellent ionic conductivity, significant thermal and electrochemical stability, and non-volatility. These unique properties make ion gels widely used in functional materials, sensors, flexible electronics, solid electrolytes, and biomedicine. Ionic liquids are confined in polymer networks to prepare ionic liquid gels.
[0003] CdS semiconductor quantum dots are a promising photocatalyst, but they also have inherent defects, such as high surface energy that easily leads to agglomeration, which affects their catalytic performance and is not conducive to recycling. In addition, photocorrosion, a common problem of semiconductor materials, is particularly serious in quantum dots, which affects the reuse rate of materials. It is reported that ionic liquids have the effect of effectively preventing photocorrosion of quantum dot semiconductors. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an ion gel composite material to address the technical problems such as low catalytic efficiency of semiconductor quantum dots and susceptibility of semiconductors to light corrosion. At the same time, the method can effectively prevent the loss of ionic liquids to form an ion liquid gel composite material.
[0005] To achieve the above-mentioned purpose of the present invention, a method for preparing semiconductor ion gel microspheres of the present invention is implemented by the following steps:
[0006] (1) Preparation of semiconductor quantum dot solution: CdCl2·2.5H2O and 3-mercaptopropionic acid were added to a certain amount of water and stirred until fully dissolved, and a 30% mass fraction NaOH solution was added to adjust the pH to >10;
[0007] (2) Deoxygenation reaction: The solution is placed in a flask and nitrogen is introduced for a certain period of time. A certain amount of Na2S is added and heated. The temperature is naturally lowered after the reaction is completed.
[0008] (3) separation and impurity removal: adding a certain volume of acetone to the solution, centrifuging and repeatedly washing, obtaining CdS semiconductor quantum dots and then configuring them into a CdS semiconductor quantum dot aqueous solution;
[0009] (4) Mixing: adding ionic liquid, acrylamide, and N,N-methylenebisacrylamide to a certain amount of CdS semiconductor quantum dot aqueous solution and ultrasonically forming an aqueous phase, adding a certain amount of Span 80 and Tx-100 to cyclohexane and ultrasonically forming an oil phase, and then slowly dripping the aqueous phase into the oil phase and ultrasonically mixing;
[0010] (5) Inverse emulsion polymerization: heating the above oil bath for polymerization for a certain period of time and naturally cooling to room temperature;
[0011] (6) Washing and drying: Add ethanol to the obtained emulsion, stir and centrifuge, wash it multiple times, and freeze-dry it.
[0012] As a preferred embodiment of the above preparation method, in step (1), the molar ratio of CdCl2·2.5H2O to 3-mercaptopropionic acid is 1:1.2 to 1:3.
[0013] As a preferred embodiment of the above preparation method, in step (1), the molar ratio of CdCl2·2.5H2O to water after pH adjustment is 1:1000 to 1:2000.
[0014] As a preferred embodiment of the above preparation method, in step (2), the molar ratio of CdCl2·2.5H2O to Na2S is 1:0.8 to 1:1.2.
[0015] As a preferred embodiment of the above preparation method, in step (3), the volume ratio of the solution to the acetone solution is 1:1.2 to 1:2.
[0016] As a preferred embodiment of the above preparation method, in step (3), the amount of water added to prepare the aqueous solution is more than 200 times the molar amount of CdCl2·2.5H2O.
[0017] As a preferred embodiment of the above preparation method, in step (4), the mass ratio of acrylamide to ionic liquid is 2:1 to 6:1.
[0018] As a preferred embodiment of the above preparation method, the mass ratio of acrylamide to N,N-methylenebisacrylamide added in step (4) is 200:1 to 50:1.
[0019] As a preferred embodiment of the above preparation method, the mass ratio of acrylamide to the CdS semiconductor quantum dot aqueous solution added in step (4) is 1:2 to 1:3.
[0020] As a preferred embodiment of the above preparation method, in step (4), the mass ratio of Span 80 to Tx-100 is 5:1 to 3:1.
[0021] As a preferred embodiment of the above preparation method, the volume ratio of the water phase to the oil phase in step (4) is 2.5:1 to 5:1.
[0022] As a preferred embodiment of the above preparation method, the heating temperature in step (5) is 70-75° C. and the polymerization time is 3-6 hours.
[0023] Compared with the prior art, this invention has a method for preparing semiconductor ion gel microspheres, which has the following beneficial effects:
[0024] The invention adopts CdCl2·2.5H2O as a cadmium source, uses 3-mercaptopropionic acid as a ligand, adjusts pH by using a NaOH solution, heats the reaction and uses water as a solvent to simply prepare CdS semiconductor quantum dots.
[0025] The present invention uses acrylamide as a monomer to polymerize and form a polymer network structure, confines the ionic liquid in the pores of the mesoporous titanium dioxide, and improves the catalytic ability of the semiconductor quantum dots.
[0026] The invention adopts reverse emulsion polymerization to successfully prepare semiconductor ion gel composite microspheres with large specific surface area, low fluidity and ion liquid that is not easy to be leached and lost.
[0027] The preparation process of the invention is simple, the preparation cycle is short, the preparation cost is low, and it can be adapted to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 1 is a SEM image of semiconductor ion gel microspheres prepared by Example 1 and Example 2 of the method of the present invention;
[0029] Figure 2 is a TEM image of semiconductor ion gel microspheres prepared in Example 1 of the method of the present invention;
[0030] Figure 3 FT-IR graph of semiconductor ion gel microspheres prepared by the method Example 1 of the present invention and its constituent materials;
[0031] Figure 4 It is the Zeta potential diagram of the semiconductor ion gel microspheres prepared by Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the method of the present invention. DETAILED DESCRIPTION
[0032] To describe the present invention, the preparation method of semiconductor ion gel microspheres of the present invention is further described in detail below in conjunction with examples. However, the present invention is not limited to the examples.
[0033] Example 1
[0034] (1) Preparation of semiconductor quantum dot solution: 4 mmol CdCl2·2.5H2O and 6.8 mol 3-mercaptopropionic acid were added to 4.4 mmol water and stirred until fully dissolved, and 30% NaOH solution was added to adjust the pH to > 10;
[0035] (2) Deoxygenation reaction: The solution was placed in a flask and nitrogen was introduced for a certain period of time. 4 mmol of Na2S was added and heated. The temperature was naturally lowered after the reaction was completed.
[0036] (3) separation and impurity removal: adding a certain volume of acetone to the solution, centrifuging and repeatedly washing, wherein the volume ratio of acetone to water during washing is greater than 1.5, and after obtaining CdS semiconductor quantum dots, a CdS semiconductor quantum dot aqueous solution is prepared;
[0037] (4) Mixing: Add ionic liquid, acrylamide, and N,N-methylenebisacrylamide to a certain amount of CdS semiconductor quantum dot aqueous solution and ultrasonically form an aqueous phase. The ionic liquid is [Bmim]BF4, wherein the mass of acrylamide is 4g, the mass of ionic liquid is 1g, the mass of N,N-methylenebisacrylamide is 0.04g, and the mass of CdS semiconductor quantum dot aqueous solution is 10g. Add a certain amount of Span 80 and Tx-100 to cyclohexane to ultrasonically form an oil phase, then slowly drop the aqueous phase into the oil phase and ultrasonically mix; wherein the mass of Span 80 is 3.2g, the mass of Tx-100 is 0.8g, and the volume of cyclohexane is 25ml.
[0038] (5) Inverse emulsion polymerization: The mixed solution was heated in an oil bath to 70°C for 5 h and then naturally cooled to room temperature;
[0039] (6) Washing and drying: The obtained emulsion was washed three times with ethanol and dried in a vacuum drying oven at 50°C for 12 h.
[0040] Example 2
[0041] (1) Preparation of semiconductor quantum dot solution: 4 mmol CdCl2·2.5H2O and 6.8 mol 3-mercaptopropionic acid were added to 4.4 mmol water and stirred until fully dissolved, and 30% mass fraction NaOH solution was added to adjust the pH to > 10;
[0042] (2) Deoxygenation reaction: The solution was placed in a flask and nitrogen was introduced for a certain period of time. 4 mmol of Na2S was added and heated. The temperature was naturally lowered after the reaction was completed.
[0043] (3) separation and impurity removal: adding a certain volume of acetone to the solution, centrifuging and repeatedly washing, wherein the volume ratio of acetone to water during washing is greater than 1.5, and after obtaining CdS semiconductor quantum dots, a CdS semiconductor quantum dot aqueous solution is prepared;
[0044] (4) Mixing: Add ionic liquid, acrylamide, and N,N-methylenebisacrylamide to a certain amount of CdS semiconductor quantum dot aqueous solution and ultrasonically form an aqueous phase. The ionic liquid is [Bmim]BF4, wherein the mass of acrylamide is 4g, the mass of ionic liquid is 1.5g, the mass of N,N-methylenebisacrylamide is 0.04g, and the mass of CdS semiconductor quantum dot aqueous solution is 10g. Add a certain amount of Span 80 and Tx-100 to cyclohexane to ultrasonically form an oil phase, then slowly drop the aqueous phase into the oil phase and ultrasonically mix; wherein the mass of Span 80 is 3.2g, the mass of Tx-100 is 0.8g, and the volume of cyclohexane is 30ml.
[0045] (5) Inverse emulsion polymerization: The mixed solution was heated in an oil bath to 70°C for 5 h and then naturally cooled to room temperature;
[0046] (6) Washing and drying: The obtained emulsion was washed three times with ethanol and dried in a vacuum drying oven at 50°C for 12 h.
[0047] Comparative Example 1
[0048] (1) Mixing: Add acrylamide and N,N-methylenebisacrylamide to an aqueous solution and ultrasonically form an aqueous phase, wherein the mass of water in the acrylamide aqueous solution is 10 g, the mass of acrylamide is 4 g, and the mass of N,N-methylenebisacrylamide is 0.04 g. Add a certain amount of Span 80 and Tx-100 to cyclohexane to ultrasonically form an oil phase, then slowly drop the aqueous phase into the oil phase and ultrasonically mix, wherein the mass of Span 80 is 3.2 g, the mass of Tx-100 is 0.8 g, and the volume of cyclohexane is 25 ml.
[0049] (2) Inverse emulsion polymerization: The mixed solution was heated in an oil bath to 70°C for 5 h.
[0050] (3) Washing and drying: The obtained emulsion was washed three times with ethanol and dried in a vacuum drying oven at 50°C for 12 h.
[0051] Comparative Example 2
[0052] (1) Mixing: Ionic liquid, acrylamide, and N,N-methylenebisacrylamide are added to an aqueous solution and ultrasonically formed into an aqueous phase, wherein the ionic liquid is [Bmim]BF4, the mass of water is 10g, the mass of acrylamide is 4g, the mass of the ionic liquid is 1g, and the mass of N,N-methylenebisacrylamide is 0.04g. A certain amount of Span 80 and Tx-100 are added to cyclohexane and ultrasonically formed into an oil phase, and then the aqueous phase is slowly added dropwise to the oil phase and ultrasonically mixed, wherein the mass of Span 80 is 3.2g, the mass of Tx-100 is 0.8g, and the volume of cyclohexane is 25ml.
[0053] (2) Inverse emulsion polymerization: The mixed solution was heated in an oil bath to 70°C for 5 h.
[0054] (3) Washing and drying: The obtained emulsion was washed three times with ethanol and dried in a vacuum drying oven at 50°C for 12 h.
[0055] Comparative Example 3
[0056] (1) Preparation of semiconductor quantum dot solution: 4 mmol CdCl2·2.5H2O and 6.8 mol 3-mercaptopropionic acid were added to 4.4 mmol water and stirred until fully dissolved, and 30% NaOH solution was added to adjust the pH to > 10;
[0057] (2) Deoxygenation reaction: The solution was placed in a flask and nitrogen was introduced for a certain period of time. 4 mmol of Na2S was added and heated. The temperature was naturally lowered after the reaction was completed.
[0058] (3) separation and impurity removal: adding a certain volume of acetone to the solution, centrifuging and repeatedly washing, wherein the volume ratio of acetone to water during washing is greater than 1.5, and after obtaining CdS semiconductor quantum dots, a CdS semiconductor quantum dot aqueous solution is prepared;
[0059] (4) Mixing: Add acrylamide and N,N-methylenebisacrylamide to a certain amount of CdS semiconductor quantum dot aqueous solution and ultrasonically form an aqueous phase, wherein the mass of acrylamide is 4 g, the mass of N,N-methylenebisacrylamide is 0.04 g, and the mass of CdS semiconductor quantum dot aqueous solution is 10 g. Add a certain amount of Span 80 and Tx-100 to cyclohexane to ultrasonically form an oil phase, then slowly drop the aqueous phase into the oil phase and ultrasonically mix; wherein the mass of Span 80 is 3.2 g, the mass of Tx-100 is 0.8 g, and the volume of cyclohexane is 25 ml.
[0060] (5) Inverse emulsion polymerization: The mixed solution was heated in an oil bath to 70°C for 5 h and then naturally cooled to room temperature;
[0061] (6) Washing and drying: The obtained emulsion was washed three times with ethanol and dried in a vacuum drying oven at 50°C for 12 h.
[0062] Figure 1 : SEM images of the semiconductor ion gel microspheres prepared in Example 1 and Example 2 (Figure A Example 1, Figure B Example 2). As the ionic liquid content increases, the semiconductor gel microspheres gradually become more viscous from being relatively dispersed, and microspherical semiconductor gel polymers are successfully prepared.
[0063] Figure 2Transmission electron microscopy (TEM) of the semiconductor ion gel microspheres prepared in Example 1 showed that the prepared CdS-MPA was distributed on the gel microspheres, indicating that CdS-MPA was successfully loaded onto the semiconductor gel microspheres.
[0064] Figure 3 The FT-IR image of the semiconductor ion gel microspheres prepared from Example 1 and its constituent materials. The analysis revealed that the 3-mercaptopropionic acid at 2566 cm -1 The SH bond at 1718 cm -1 A strong peak appears at 1718 cm, which is caused by the stretching vibration of C=O. However, this peak disappears in the quantum dots, so we speculate that the -COOH in the ligand molecule has also changed, producing sodium carboxylate. -1 No absorption, but at 1604 and 1403 cm -1 At the same time, we detected [Bmim]BF4 at 1052 cm-1 in FT-IR in Example 1. -1 The broad peak of BF at , indicates that the product obtained in Example 1 contains the substance [Bmim]BF4, and the product is finally successfully prepared.
[0065] Figure 4 The Zeta potential analysis results of Example 1, Control Example 1, Control Example 2, and Control Example 3 are shown in Figure 1. Zeta potential can reflect the surface charge density of colloidal particles. The change in the Zeta potential of the material surface can be used to determine whether the charged component is compounded into the matrix material. The Zeta potential of Control Example 1 is -10.51mV. After [Bmim]BF4 is loaded onto PAM, the surface potential of Control Group 2 is -2.23mV, which is 8.28mV higher than that of Control Example 1. This indicates that the doping of ionic liquids will increase the potential of the product. Similarly, when CdS-MPA is added, Control Example 3 is reduced by 9.66mV compared with Control Example 1, which indicates that the presence of CdS-MPA reduces its surface potential.
Claims
1. A method for preparing semiconductor ion gel microspheres, characterized in that: The following steps are involved: (1) Preparation of semiconductor quantum dot solution: CdCl2·2.5H2O and 3-mercaptopropionic acid were added to a certain amount of water and stirred until fully dissolved, and a 30% mass fraction NaOH solution was added to adjust the pH to >10; (2) Deoxygenation reaction: The solution is placed in a flask and nitrogen is introduced for a certain period of time. A certain amount of Na2S is added and heated. The temperature is naturally lowered after the reaction is completed. (3) separation and impurity removal: adding a certain volume of acetone to the solution, centrifuging and repeatedly washing, obtaining CdS semiconductor quantum dots and then configuring them into a CdS semiconductor quantum dot aqueous solution; (4) Mixing: adding ionic liquid, acrylamide, and N,N-methylenebisacrylamide to a certain amount of CdS semiconductor quantum dot aqueous solution and ultrasonically forming a water phase, adding a certain amount of Span 80 and Tx-100 to cyclohexane and ultrasonically forming an oil phase, slowly dropping the water phase into the oil phase and then ultrasonically mixing; (5) Inverse emulsion polymerization: The mixed solution is heated in an oil bath for polymerization for a certain period of time and then naturally cooled to room temperature; (6) Washing and drying: Add ethanol to the obtained emulsion, stir and centrifuge, wash it multiple times, and dry it in a vacuum oven.
2. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (1), the molar ratio of CdCl2·2.5H2O to 3-mercaptopropionic acid is 1:1.2 to 1:
3.
3. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (1), the molar ratio of CdCl2·2.5H2O to water after pH adjustment is 1:1000 to 1:2000.
4. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (2), the molar ratio of CdCl2·2.5H2O to Na2S is 1:0.8 to 1:1.2, and the amount of water added to the aqueous solution is more than 200 times the amount of CdCl2·2.5H2O.
5. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (4), the ionic liquid is [Bmim]BF4.
6. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (4), the mass ratio of acrylamide to ionic liquid is 2:1 to 6:1, the mass ratio of acrylamide to N,N-methylenebisacrylamide is 200:1 to 50:1, and the mass ratio of acrylamide to CdS semiconductor quantum dot aqueous solution is 1:2 to 1:
3.
7. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (4), the mass ratio of Span 80 to Tx-100 is configured to be 5:1 to 3:
1.
8. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (4), the volume ratio of the water phase to the oil phase is configured to be 2.5:1 to 5:
1.
9. The method for preparing semiconductor ion gel microspheres according to claim 1, characterized in that: In step (5), the heating temperature is 70-75° C. and the polymerization time is 3-6 hours.
Citation Information
Patent Citations
Preparation method for ionic-liquid-modified carbon quantum dot
CN105315993A
Straw cellulose hydrogel-CdS nano-quantum dot compound and preparation method thereof
CN107915867A
Ionic gel material based on oil-soluble carbon quantum dots and preparation method of ionic gel material
CN111607389A
Quantum dot fluorescent microsphere and preparation method thereof
CN111944191A
Preparation method of ionic liquid gel nanospheres containing carbon dots and application of ionic liquid gel nanospheres in fluorescence detection
CN115651646A